THE EFFECT OF COUNTRY OF ORIGIN AND PERCEIVED QUALITY ON PURCHASE INTENTION (BRAND IMAGE AS THE MEDIATING ROLE CASE STUDY : VIVO SMARTPHONE IN PONTIANAK) - dini, Dini Dwi Damayanti B1024131002 (Jurnal Manajemen Update, 2018)
THE EFFECT OF COUNTRY OF ORIGIN AND PERCEIVED QUALITY ON PURCHASE INTENTION (BRAND IMAGE AS THE MEDIATING ROLE CASE STUDY : VIVO SMARTPHONE IN PONTIANAK) ABSTRACTAs the impact of technology many producers of smartphone in international scale are compete to win the market competition also becoming the main option and embedded in customer mind. Including in technology sector by doing innovation and invention in order to be choosen by the customers. the last decades people only know about cell phone or handphone just has limited function. But today is already change to be smartphone that has so many function to fulfill the customer needs so it needed the smartphone with fast and precise. Recently, the producers of smartphone from China do massive marketing to increase the brand presence in the market. There are several factors that can be determinant of success to create the purchase intention among those, Country of Origin, Perceived Quality, and Brand Image that appeared on each individual. Brand image is also become the mediating role. In this research are using questionnaires as the main research instument. The research are conduct 100 respondents in Pontianak city were selected based on purposive sampling. SPSS 17.0 software used to complete the quantitative data. The result show that Perceived Quality has significant influence on brand image, country of origin, perceived quality and brand image also has significant influences on purchase intention. However, country of origin didn?t give any significant influences result on brand image of Vivo Smartphone in Pontianak.Keywords : Country of Origin, Perceived Quality, Brand Image and Purchase Intention.